IMPLEMENTASI LITERASI DIGITAL DI SEKOLAH : TINJAUAN PUSTAKA SISTEMATIS - Dewi, Khristi Rosika; Heru Subrata; Ari Metalin Ika Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digital literacy is characterized as the competence to understand and utilize information presented in various formats from various sources accessed through computing devices. This research aims to conduct a literature review related to the implementation of school digital literacy. The research method is SLR (Systematic Literature Review). Data collection was done by reviewing the same articles in this study. The articles used in this study were 11 articles from google scholar, national and international indexed journals. This study found that technology can be implemented in school learning, and digital literacy can increase students' interest in reading. Keywords: implementation, digital literacy, school